2014
DOI: 10.1063/1.4864261
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and transport properties of zigzag graphene nanoribbons/hexagonal boron nitride heterostructures

Abstract: Results of ab initio study of magnetism and transport properties of charge carriers in zigzag graphene nanoribbons (ZGNR) on hexagonal boron nitride (h-BN(0001)) substrate are presented within the density functional theory framework. Peculiarities of the interface band structure and its role in the formation of magnetism and transport properties of the ZGNR/h-BN(0001) heterostructure have been studied using two different density functional approximations. The effect of the substrate and graphene nanoribbons wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…We have noted that, the substrate significantly varies magnetic and transport properties of ZGNRs. 38 In particular, it was also shown that the influence of the substrate on electronic properties of the heterostructure increases with decreasing GNR width. 38 In this study showed that the degeneration in energy of the edge localized states is removed when E ext is applied.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have noted that, the substrate significantly varies magnetic and transport properties of ZGNRs. 38 In particular, it was also shown that the influence of the substrate on electronic properties of the heterostructure increases with decreasing GNR width. 38 In this study showed that the degeneration in energy of the edge localized states is removed when E ext is applied.…”
Section: Discussionmentioning
confidence: 97%
“…38 In particular, it was also shown that the influence of the substrate on electronic properties of the heterostructure increases with decreasing GNR width. 38 In this study showed that the degeneration in energy of the edge localized states is removed when E ext is applied. In ZGNR/h-BN(0001) heterostructure, value of this splitting energy was higher than one in ZGNRs without substrate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Usually, the ferromagnetic properties of these structures are associated with the presence of spin asymmetry of valence electrons, which is realized by two mechanisms: 1) impurities of other elements; 2) quasi-regular defects of the carbon structure (for example, graphene nanoribbons (GNR)) [9]. The boundary geometry is responsible for the spin density asymmetry at the GNR edges, which is confirmed by the results given in the works [10,11]. As exemplified by ZGNR/h-BN(0001) heterostructures , the spin magnetic moments (MM) of 0,27 B , are induced at the edges, which is more than an order of magnitude higher than that of other carbon atoms.…”
mentioning
confidence: 85%
“…As exemplified by ZGNR/h-BN(0001) heterostructures , the spin magnetic moments (MM) of 0,27 B , are induced at the edges, which is more than an order of magnitude higher than that of other carbon atoms. The authors of [10,11] attributed the nature of magnetism to the violation of the symmetry breaking of the sublattices A and B of graphene caused by the deformation of the C-C bond length at the edges of the nanoribbon. It is known [12] that the magnetic state of graphene nanoribbons is characterized by a lower energy than the nonmagnetic state.…”
mentioning
confidence: 99%